Prolonged sampling of spontaneous sputum improves sensitivity of hypermethylation analysis for lung cancer. Issue 6 (29th March 2012) - Hubers, A Jasmijn; Heideman, Daniëlle A M; Herder, Gerarda J M; Burgers, Sjaak A; Sterk, Peter J; Kunst, Peter W; Smit, Henk J; Postmus, Pieter E; Witte, Birgit I; Duin, Sylvia; Snijders, Peter J F; Smit, Egbert F; et al.
Abstract : Aims: The adequacy of lung cancer diagnosis with sputum cytology depends on duration of sputum sampling. The aim of this methodological study was to determine whether the hypermethylation detection rate of RASSF1A, adenomatous polyposis coli (APC) and cytoglobin (CYGB) is influenced by the duration of sputum collection. Methods: Prospective sputum samples were collected from 53 lung cancer patients and 47 chronic obstructive pulmonary disease patients as controls. Subjects collected spontaneous sputum at home during nine consecutive days in three canisters I, II and III (ie, days 1–3, days 4–6, days 7–9, respectively). Quantitative methylation-specific PCR was performed to assess gene promoter methylation status of RASSF1A, APC and CYGB. Results: Analysis of each canister separately showed hypermethylation of RASSF1A, APC and/or CYGB in samples I, II and III, in 43%, 40% and 47% of cases, respectively. In control samples, these numbers were 4%, 2% and 4%, respectively. Cumulative analysis for days 1–6 and days 1–9 revealed an increase in sensitivity to 53% and 64%, and specificity of 94% and 91%, respectively. Conclusion: Sputum collected over multiple successive days results in a gain in sensitivity for the detection of lung cancer, at the expense of a small loss in specificity. Condensed abstract: Assessment of hypermethylation sensitivity of biomarkers in sputum collected over a prolonged period for the detection of lung cancer resulted in a promising gain in sensitivity, at the expense of a small loss in specificity.